PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBIMBING ANAK DARI KELUARGA BROKEN HOME DI SEKOLAH - Orvi Ba’un (CV. Adiba Aisha Amira, 2025)
Children from broken home families often face emotional stress and lack of attention, which negatively affects their behavior and academic performance at school. In such situations, the role of Christian Religious Education (CRE) teachers becomes crucial in providing spiritual and emotional guidance. CRE teachers are not only responsible for teaching biblical knowledge but also serve as role models who offer love, understanding, and moral support. Through a holistic approach, CRE teachers can help students overcome emotional wounds, rebuild self-confidence, and instill Christian values in their daily lives. The methods used include pastoral counseling, character-building lessons, and empathetic relationships. In doing so, CRE teachers play an active role in shaping strong and resilient character in children, despite their broken family background. This article explores the practical strategies and challenges faced by Christian Religious Education teachers in guiding broken home students in a school environment.